2017
DOI: 10.1016/bs.enz.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

TrmD

Abstract: TrmD is an S-adenosyl methionine (AdoMet)-dependent methyl transferase that synthesizes the methylated m1G37 in tRNA. TrmD is specific to and essential for bacterial growth, and it is fundamentally distinct from its eukaryotic and archaeal counterpart Trm5. TrmD is unusual by using a topological protein knot to bind AdoMet. Despite its restricted mobility, the TrmD knot has complex dynamics necessary to transmit the signal of AdoMet binding to promote tRNA binding and methyl transfer. Mutations in the TrmD kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…3C,D). Although the catalytic mechanism that was proposed for the majority of SAM-dependent methyl transferases requires no divalent metal ions, Sakaguchi et al reported that TrmD-catalyzed methyl transfer from SAM to the N 1 atom of G37 from the tRNA is strongly dependent on the presence of divalent metal ions, with Mg 2+ as the most physiologically relevant (Sakaguchi et al 2014;Hou et al 2017). Based on the pH-activity profile, they proposed a catalytic mechanism in which Mg 2+ increases the nucleophilicity of N 1 of G37 and stabilizes the developing negative charge on O 6 during an attack on the methyl sulfonium of the SAM donor.…”
Section: Features Of Patrmd Bound To Sam and Sfgmentioning
confidence: 99%
See 1 more Smart Citation
“…3C,D). Although the catalytic mechanism that was proposed for the majority of SAM-dependent methyl transferases requires no divalent metal ions, Sakaguchi et al reported that TrmD-catalyzed methyl transfer from SAM to the N 1 atom of G37 from the tRNA is strongly dependent on the presence of divalent metal ions, with Mg 2+ as the most physiologically relevant (Sakaguchi et al 2014;Hou et al 2017). Based on the pH-activity profile, they proposed a catalytic mechanism in which Mg 2+ increases the nucleophilicity of N 1 of G37 and stabilizes the developing negative charge on O 6 during an attack on the methyl sulfonium of the SAM donor.…”
Section: Features Of Patrmd Bound To Sam and Sfgmentioning
confidence: 99%
“…While these modifications are widely distributed throughout the tRNA molecule and affect ∼10% of the ∼80-90 tRNA nucleotides, modifications at positions 32, 34, and 37 are recognized for their role in regulating cellular stress responses (Begley et al 2007;Chan et al 2012;Chionh et al 2016;Jaroensuk et al 2016) and promoting antibiotic resistance (Taylor et al 1998). In this regard, the tRNA (m 1 G37) methyltransferase TrmD (Byström and Björk 1982;Hjalmarsson et al 1983;Hou et al 2017), which is essential in most bacterial species (Hagervall et al 1993;Forsyth et al 2002;Björk and Nilsson 2003;O'Dwyer et al 2004;de Berardinis et al 2008;Winsor et al 2011), has emerged as an important target for drug development (Lahoud et al 2011;Hill et al 2013;Baumgartner and Camacho 2016). TrmD uses S-adenosylmethionine (SAM) as a methyl donor and catalyzes the methylation of G37 to form 1methylguanosine (m 1 G) mainly in tRNAs containing a G36G37 motif, thus reading codons that start with C, including those for leucine (CUN), proline (CCN), and arginine (CCG) (Björk et al 2001;Sprinzl and Vassilenko 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One exception is the N 1 -methylation of G37 on the 3′-side of the tRNA anticodon, generating m 1 G37 (Figure 1A), which as a single methylated nucleobase is not only essential for life but is also conserved in evolution present in all three domains of life (Bjork et al, 2001). In the bacterial domain, the biosynthesis of m 1 G37 is catalyzed by the tRNA methyl transferase TrmD (Hou et al, 2017), whereas in the eukaryotic and archaeal domains, it is catalyzed by Trm5 (Bjork et al, 2001). While both TrmD and Trm5 perform the same methyl transfer reaction, using S -adenosyl methionine (AdoMet) as the methyl donor, they are fundamentally different in structure, where TrmD is a member of the SpoU-TrmD family (Anantharaman et al, 2002; Ahn et al, 2003; Elkins et al, 2003; Ito et al, 2015; Hori, 2017) and Trm5 is a member of the Rossmann-fold family (Goto-Ito et al, 2008, 2009).…”
Section: The M1g37-methylation In Trnamentioning
confidence: 99%
“…We have shown that Gram-negative bacteria E. coli and Salmonella, when in deficiency of m 1 G37-tRNA, suffer from damaged cell envelope with reduced biosynthesis of IM and OM proteins (Masuda et al, 2019). Throughout both Gram-negative and Gram-positive bacteria, the tRNA methyl transferase TrmD is the conserved enzyme that synthesizes m 1 G37-tRNA, using S-adenosyl-methionine (AdoMet) as the methyl donor (Christian, Evilia, Williams, & Hou, 2004;Hou, Matsubara, Takase, Masuda, & Sulkowska, 2017). TrmD is essential for bacterial growth and survival, because its disruption leads to accumulation of +1 frameshifting and causes cell death (Gamper et al, 2015a).…”
Section: Deficiency Of M 1 G37 Damages Gram-negative Cell Envelopementioning
confidence: 99%